Determinants Of Cost Efficiency In Malaysian Banking - Rossazana Ab-Rahim, Ab-Rahim; Nor Ghani, Md. Nor; Shamsubaridah, Ramlee; Nur Zaimah, Ubaidillah (Universiti Malaysia Sarawak (UNIMAS), 2012)
This study estimates the cost efficiency and its decompositions of Malaysian banks over the period of 1995 to 2010 by utilising data envelopment analysis (DEA) method. Instead of estimating efficiency based on DEA separate frontiers approach; this study departs from practice of many previous studies by pooling the data set to build a DEA common frontier. This study contributes to the existing literature by integrating determinants of banking efficiency into the areas of DEA methodology in the context of Malaysian banking system across individual domestic banks. The first objective of this study is to estimate cost efficiency and its decompositions, which are technical and allocative efficiency as well as to estimate sources of technical efficiency namely pure technical efficiency and scale efficiency. Next, Tobit regression analysis is undertaken to identify the determinants of various measures of banking efficiency. The results indicate that government ownership, population density, demand density and market concentration are positively associated with several measures of efficiency while year that merger takes place, macroeconomic condition, capitalization, credit risk, asset quality and management quality have a negative relationship with various measures of efficiency. However, the size of banks is found to have mixed sign, positive coefficient with technical and pure technical efficiency while the negative relationship with scale efficiency, cost and allocative efficiency.